ANALISIS PEMBATALAN PERKAWINAN KARENA PENIPUAN PERNIKAHAN SAH TANPA WALI MENURUT PERSPEKKTIF HUKUM ISLAM - Khusni Alfiyan (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2022)
Marriage is something that cannot be separated from human life because as living beings humans are created in pairs. In Islam, marriage has a meaning as a form of worship to Allah and as a form of following the sunnah of the Prophet. Islamic law has a very important position because it regulates the law regarding marriage, which regulates family procedures which are the goal of living in a society. Marriage law is part of religious teachings that must be obeyed and carried out in accordance with the provisions contained in the Qur'an and hadith. However, in reality there are still many Islamic laws that are violated, one of which is in the case of marriage which causes the marriage to be disabled or damaged, as in the case of the Kendal Religious Court Decision Number 2389/Pdt.G/2020/PA.Kdl. who decides the annulment of the marriage. This study used a qualitative method by collecting data through primary data, namely decisions and interviews with informants, which were then analyzed using Islamic law. The research found that the marriage was invalid because it did not fulfill one of the pillars of marriage, namely without a marriage guardian, so according to Islamic law the marriage could be annulled.